Wilbur R. Knorr on Thābit ibn Qurra: A Case-Study in the Historiography of Premodern Science - Brentjes, Sonja (Aestimatio, 2020)
There was a widespread belief among historians of science of my generation that high competence with regard to content and languages alone can guarantee better, more reliable results than can good philology combined with high competence in history or the other human sciences. In my casestudy of Wilbur R. Knorr’s analysis of several medieval Arabic and Latin texts on the balance, or steelyard, I highlight a variety of factors that compromised time and again his understanding and interpretation of his chosen texts. I conclude that a greater openness to more complex historiographical assumptions and more sophisticated methodological approaches as well as a greater willingness to contextualize documents in numerous dimensions before coming to conclusions about their specific meaning is crucial if we are to correct and improve upon work such as Knorr’s analysis of the Kitab al-qarastun, ascribed to Thābit ibn Qurra, and the Liber de canonio. The way forward is to enhance and temper philological analysis with solid analysis of scientific content within its relevant contexts.